Drug Related Problems (DRPs) penggunaan obat antidiabetik pada pasien rawat inap diabetes mellitus tipe 2 - Latief, Mutawalli Sjahid (PT WIM Solusi Prima, 2024)
rates continue to rise annually. Indonesia ranks fifth globally in the number of diabetes cases. Drug-related problems (DRPs) are common in clinical practice and can occur at all stages of the treatment process. Objective: This study aims to identify DRPs in hospitalized patients with Type 2 Diabetes Mellitus. Methods: This descriptive study employed a cross-sectional approach. Data were collected retrospectively from medical records of 61 hospitalized patients with Type 2 Diabetes Mellitus at a hospital in Jakarta. Results: The analysis of DRPs in hospitalized patients with Type 2 Diabetes Mellitus revealed that 5 cases (14%) involved inappropriate drug selection, 6 cases (17%) involved suboptimal dosing, 10 cases (29%) involved adverse drug reactions (ADRs), and 14 cases (40%) involved drug interactions. Conclusion: Polypharmacy requires careful attention as it has the potential to cause drug interactions and adverse drug reactions.